A CONCEPTUAL FRAMEWORK FOR IDENTIFYING SUSTAINABLE BUSINESS PRACTICES OF MALAYSIAN SMALL AND MEDIUM ENTERPRISES (SMES) - Chin, Tay Lee; Amy, Yeo Chu May; Ling, Chow Poh (Graduate Program of Universitas Tarumanagara, 2025)
Malaysian Small and Medium Enterprises’ (SMEs) Sustainable Business Practices (SBP) effort remains limited despite embracing SBP can address stakeholder expectations, minimize their social and environmental footprint over the long term. Hence, this paper identifies the factors that could enhance SBP in the Malaysian SMEs context. This study utilized a systematic review of previous studies on SBP specifically for SMEs. This study limited the literature search to journals published between 2019 and 2024 and excluded non-English articles, reports from consultancy firms, master’s and doctoral theses and government reports. The results showed that government initiatives, Human Resource Management (HRM) practices, firm and owner characteristics, technology integration and financial resources influence SBP. It contributes to the body of knowledge by providing a theoretical framework on how the factors can significantly influence the effectiveness and success of SBP in the Malaysian SMEs. This paper also identifies key gaps and potential areas for further research, specifically on the existing and future aspects of SBP in the Malaysian SMEs.